GAMBARAN PENGETAHUAN PERAWAT TENTANG BANTUAN HIDUP DASAR DI RSUD BAYU ASIH PURWAKARTA TAHUN 2022 - Wirdan Fauzi R; Sherly, Sherly (Jurnal Cakrawala Ilmiah, 2022)
Basic life support is an action or effort that is first carried out in an emergency condition to maintain life when the patient experiences a life-threatening condition. Cardiac Pulmonary Resuscitation (CPR) is an emergency measure, in an effort to restore the state of respiratory arrest or cardiac arrest to optimal function, in order to prevent biological death. This study aims to describe the knowledge of nurses about basic life support based on the 2015 AHA in the IGD of RSUD Bayuasih Purwakarta. The type of research used is descriptive research with a cross sectional design. The sampling technique used Total Sampling as many as 28 respondents using a questionnaire instrument. The results showed that the majority of respondents had knowledge of basic life support based on the 2015 AHA, namely 17 people (60.7%) had good knowledge, while 7 people (25 .0%), and less knowledgeable as many as 4 people (14.3%). Based on the results of this study, it is expected to further increase the knowledge of nurses about basic life support based on the 2015 AHA